INTERPERSONAL MEANINGS IN MICHELLE OBAMA’S SPEECH AT MEMORIAL SERVICE FOR Dr. MAYA ANGELOU (A Descriptive Qualitative Study) (English Dapartment, Faculty of Languages and Arts, Universitas Negeri Semarang, 2016)
This study investigated the interpersonal meaning which lies on the eulogy speech which was delivered by Michelle Obama at Dr. Maya Angelou’s memorial service. The purposes of this study were to describe the tenor realized in the text, the construction of the interpersonal meaning and the contribution of this study for language education. This study was categorized as a discourse analysis which used qualitative approach as its main method. The qualitative approach was used to describe the quantitative data which was got from the analysis. The data for this study was analyzed using two units of analysis. In terms of grammar analysis, the units of analysis were the MOOD system, modality, and mood types, while the lexical analysis mainly analyzed the appraisal of the speech. Based on those analysis, it can be concluded that the tenor that was realized in the speech showed the strong social relationship between the interactants. In term of status, she did not stand as the first lady of United States. In terms of contact, she tried to make the situation as friendly as possible. In addition, in terms of affect, she showed that she gave a strong involvement with the audiences through her speech. In terms of grammar analysis, it showed that Michelle Obama tended to represent herself as one of the black women who got inspiration from Dr. Maya Angelou. She also intended to inform the audiences about Dr. Maya Angelou’s life. The appraisal analysis showed that judgment was the most frequent appraisal system in the speech. Michelle Obama tended to give a high appraisement towards Dr. Maya Angelou’s struggle and actions during her life.